Silenced narratives of women's participation in labour and political struggle in Spain, 1960–1975. (3rd September 2019) - Bermúdez-Figueroa, Eva; Roca, Beltran
ABSTRACT: This article studies women's participation in the struggle against the dictatorship in Spain (from 1960 to 1975). Drawing on life stories of women activists from el Marco de Jerez, it examines their repertoires of actions, their frames, and the lack of recognition from both academic and political spheres. A Gramscian approach and the perspective of hegemonic masculinity contribute to explain how women organized, how represented their collective action, and why their memories have been silenced. The theoretical approach has helped to identify relations of hegemony within feminist studies and political movement.